Respuesta :
the 1 is the h and the -2 is the k
f(x) = a(x - h)^2 + k
f(x) = a(x-1)^2 -2
to find a substitute x=3, y=6 in
6= a(3-1)^2 -2
6 =a *2^2 -2
add 2 to each side
8 = 4a
a =2
f(x) = 2(x-1)^2 -2 this is the vertex form
distribute to get the standard from
f(x) = 2(x^2-2x+1) -2
2x^2 -4x+2-2
f(x) =2x^2-4x is the standard form
Choice A
for form [tex]f(x)=a(x-h)^2+k[/tex], the vertex is (h,k)
given that the vertex is (1,-2), h=1, k=-2
[tex]f(x)=a(x-1)^2-2[/tex]
find a by subsituting the given point
(3,6), x=3 and f(x)=6
[tex]6=a(3-1)^2-2[/tex]
[tex]6=a(2)^2-2[/tex]
[tex]6=4a-2[/tex]
[tex]8=4a[/tex]
[tex]2=a[/tex]
[tex]f(x)=2(x-1)^2-2[/tex]
epxnad to find standard form
[tex]f(x)=2(x^2-2x+1)-2[/tex]
[tex]f(x)=2x^2-4x+2-2[/tex]
[tex]f(x)=2x^2-4x[/tex]
vertex form is [tex]f(x)=2(x-1)^2-2[/tex]
standard form is [tex]f(x)=2x^2-4x[/tex]
answer is A